A new species of Ascidiacea (Herdmania andamanensis sp. nov.) from Andaman and Nicobar Islands, India - Mondal, Jhimli; Raghunathan, C.; Chandra, Kailash (Zootaxa, 2017)
Ascidians are the least explored fauna in Andaman and Nicobar Islands of India; only 85 species have been recorded from this area. The present paper describes a new species of ascidian, Herdmania andamanensis sp. nov. from Andaman and Nicobar Islands collected from two localities at the depth of 8–10 m. The species closely resembles Herdmania coutieri C. Monniot, 2002 and Herdmania mauritiana (Drasche, 1884), however differs in several anatomical characters which distinguishes it as a new species of the genus Herdmania.